A influência da idéia de progresso no movimento abolicionista brasileiro: o caso Joaquim Nabuco - Lamardo, Rafael (2006)
This essay A Influência da Idéia de Progresso no Movimento Abolicionista Brasileiro: o Caso Joaquim Nabuco ( The Influence of Idea of Progress on Brazilian Abolitionist Movement: the Case Joaquim Nabuco ) analyzes the abolitionist thoughts of Joaquim Nabuco focusing on the application of idea of progress on his speech. In the end of 19th century, the idea of progress influenced thoughts and philosophical chains, not only related to technical or scientific aspects, but also to the men condition in society. Joaquim Nabuco, on his book O Abolicionismo ( The Abolitionism ), articulates the question of progress, pointing out slavery as the main ground for the society stagnation